Epimysial Transposition Flap: A Novel Technique for Coverage of Exposed Tendon after Tissue Transfer - Lombana, Nicholas F.; Falola, Reuben A.; Scott, Michael; Saint-Cyr, Michel H. (Journal of Reconstructive Microsurgery Open, 2021)
Background The radial forearm flap (RFF) is a versatile flap that can be used for soft-tissue coverage or as a source of vascularized bone during reconstruction. A problem that can arise after RFF harvest is tendon exposure in the donor site, which may lead to tendon injury and restriction of the hand and wrist’s range of motion. Many different methods for providing adequate tendon coverage in the donor site after RFF harvest have been reported. We present a novel technique for coverage of exposed tendon in the volar forearm with an epimysial transposition flap and a split-thickness skin graft (STSG).Methods Retrospective review of two cases: one salvage case with exposed tendon after harvesting an RFF and another with exposed volar forearm tendon after traumatic injuries. Variables of interest were post-operative STSG integration and hand/wrist range of motion.Results Both cases demonstrated 100% graft take at 5-week follow-up. No decrease in hand/wrist range of motion in the patient that could undergo testing.Conclusion We introduce two cases for coverage of exposed flexor tendon in the volar forearm with an epimysial transposition flap. This can be used as a salvage operation for coverage of exposed tendon or as an acute method of tendon coverage prior to skin grafting. In both cases, the skin graft had excellent incorporation.
Keywords: radial forearm flap; epimysial transposition flap; upper extremity reconstruction